Women in science - Ancog, Amelia C. (1999)
Women have always been of critical importance in economic development despite studies indicating disparities in access to opportunities in science and other fields. They have been involved in diverse fields and industries such as business ventures, electronic products, textiles and garments, canned food, jewelry and footwear. They have also ventured into science and technology fields by becoming engineers and research scientists. Women also have a substantial role in agriculture and its numerous aspects like plant production, protection and soil science. Despite their extensive involvement in economic growth, women do not share inequitable terms with regards to ranks, positions and prestige in various activities relating to such. Since global competitiveness is dependent on a strong technological workforce and an environment that nurtures both men and women to contribute to new breakthroughs in policy reforms, products, facilities and services, there is a continuing need to assess the changes that are taking place at the national and regional levels.
Keywords: Women in science; Women scientists; Women in economic development; Consultative Group for International Agricultural Research (CGIAR); Engineering and Science Education Program (ESEP); Scientific Career System (SCS)